Kempei tai : - Deacon, Richard (Charles E. Tuttle, 1990)
For the first time Western readers can learn the full story of how the Secret Service enables Japan to win the Russo- Japanese War, the decisive event that propelled Japan into the modern world. Also explored is the organization's amazing pre-Pearl Harbor intelligence operations in the United States, its disintegration after World War II and, finally, its resurrection as the giant organization that works today for the economic prosperity of Japan.